Activated Carbons Derived from Date (Phoenix dactylifera) Seeds with Excellent Iodine Adsorption Properties - Mallick, Aabhash Kumar; Jha, Abhimanyu; Pokharel, Bhadra Prasad; Rajbhandari, Rinita; Shrestha, Rajeshwar Man (Journal of the Institute of Engineering, 2019)
Activated carbons were prepared from date seed powder by chemical activation method using potassium hydroxide (KOH)as activating agent at different temperatures (400, 500, 600 and 700 °C). Date seed powder was impregnated with KOH (1:1weight ratio) and carbonizations were carried out under a constant flow of nitrogen (120 cc/min) in a tubular furnace. The activated carbons thus obtained were characterized by powder X- Ray diffraction and Raman scattering. XRD patterns revealed amorphous carbon structure, which was further confirmed by the Raman scattering. Surface morphology of ACs was studied by scanning electron microscopy (SEM). Date seed derived activated carbons showed good iodine adsorption properties giving iodine number value of 850mg/g, which is much higher than the commercial activated carbons. Therefore, KOH activated date seed derived carbons would have potential in dye adsorption and waste water treatments.